Family functioning in two treatments for adolescent anorexia nervosa. Issue 1 (5th June 2014) - Ciao, Anna C.; Accurso, Erin C.; Fitzsimmons‐Craft, Ellen E.; Lock, James; Le Grange, Daniel
ABSTRACT Objective Family functioning impairment is widely reported in the eating disorders literature, yet few studies have examined the role of family functioning in treatment for adolescent anorexia nervosa (AN). This study examined family functioning in two treatments for adolescent AN from multiple family members' perspectives. Method Participants were 121 adolescents with AN ages 12–18 from a randomized‐controlled trial comparing family‐based treatment (FBT) to individual adolescent‐focused therapy (AFT). Multiple clinical characteristics were assessed at baseline. Family functioning from the perspective of the adolescent and both parents was assessed at baseline and after 1 year of treatment. Full remission from AN was defined as achieving both weight restoration and normalized eating disorder psychopathology. Results In general, families dealing with AN reported some baseline impairment in family functioning, but average ratings were only slightly elevated compared to published impaired functioning cutoffs. Adolescents' perspectives on family functioning were the most impaired and were generally associated with poorer psychosocial functioning and greater clinical severity. Regardless of initial level of family functioning, improvements in several family functioning domains were uniquely related to full remission at the end of treatment in both FBT and AFT. However, FBT had a more positive impact on several specific aspects of family functioning compared to AFT. Discussion Families seeking treatment for adolescent AN report some difficulties in family functioning, with adolescents reporting the greatest impairment. Although FBT may be effective in improving some specific aspects of family dynamics, remission from AN was associated with improved family dynamics, regardless of treatment type. © 2014 Wiley Periodicals, Inc. (Int J Eat Disord 2015; 48:81–90)